A Case Lichen Planus Pigmentosus an Uncommon Entity with Distinctive Characteristics: A Case Report - Salah, Muhammed; Shas, Muhammed; K, Nahdha; Parveen, Shariba; S, Anjali C; R, Kameswaran; K, Sirajudheen M (Indian Journal of Pharmacy Practice)
Lichen Planus Pigmentosus (LPP) is a rare variant of lichen planus that presents as dark brown to grey hyperpigmented macules over sun-exposed areas such as the face, neck, and upper limbs. This case report aims to describe an uncommon presentation of LPP in a middle-aged woman and the therapeutic challenges during its management. A 46-year-old female developed pruritic erythematous rashes on the face and arms that gradually progressed to slate-grey hyperpigmented patches over three years. A skin biopsy confirmed LPP. Initial treatment with isotretinoin and topical steroids caused adverse effects and minimal improvement. The therapy was changed to deflazacort, topical corticosteroids, and emollients, resulting in marked lesion regression with residual pigmentation. Long-term care included sun protection, moisturization, and regular follow-up. This case highlights the importance of individualized therapy and demonstrates that corticosteroids can be an effective, well-tolerated option for managing steroid-responsive LPP unresponsive to retinoids.
Keywords: Hyperpigmentation; Immune system disorder; Lichen Planus Pigmentosus; Rash and; Pruritis; Sun exposed areas